Korelasi antara kadar testosteron total dengan trans epidermal water loss (TEWL) pada pria late onset hypogonadism - Daniel Widiyanto; Reny Iâ€™tishom (DiscoverSys Inc., 2018)
Background: Late Onset Hypogonadism (LOH) is a clinical and biochemical condition in the elderly with testosterone levels below the reference value of young and healthy men, accompanied by symptoms of testosterone deficiency. Increased age or aging process is one of the factors causing sebaceous gland function decreased both regarding quantity and regarding quality associated with the function of lipid barrier. Decreased sebum gland function can be seen from several parameters, one of which is the increase of Trans Epidermal Water Loss (TEWL). Methods: This study was an observational analytic study with cross-sectional design to determine the relationship between total testosterone and TEWL in LOH men. This research was conducted in Outpatient Unit Andrology of dr. Soetomo from May 2017 to July 2017. 16 samples of elderly male patients (â‰¥60 years) were selected using the consecutive sampling technique who met the inclusion and exclusion criteria. Performed total testosterone test and TEWL level examination by using Tewameter to the research sample. Interpretation of results adjusted to Research and Development Department, Courage & Khazaka Electronics GmbH, Koln, Germany. Results: The Total testosterone levels of the patient were ranged from 146.11 - 575.10 ng/dL with a mean of 351.67 ng/dL and standard deviation of 116.34. The TEWL level of the patients was ranged from 17.2 - 50.8 g/jam/m2 with a mean of 31 g/jam/m2 and standard deviation of 9.20. The correlation coefficient value between total testosterone and TEWL was -0.853 with a significance of 0.0001 (p <0.05). Conclusion: There was a significant relationship between total testosterone and TEWL. The association of total testosterone with TEWL is unidirectional. The lower the testosterone level, the higher the TEWL value.